Etiquette Learning through the Team Teaching Model - Anwar, Saiful; In'am, Akhsanul; Faridi; Ikhwan, Afiful (LETIGES, 2025)
This study aims to provide an in-depth description of the reasons why Madrasah Ibtidaiyah Muhammadiyah 6 Nglegok employs etiquette learning through the team teaching model, as well as the process of implementing etiquette learning through this model. In this case, the main focus is the planning, implementation, and evaluation of etiquette learning through the team teaching model. This study employs a constructivist paradigm with a qualitative approach and utilizes a case study research design. Data collection uses observation, interview, and documentation techniques. Data validity employs triangulation and extended observation time in the field, along with data analysis techniques that include pattern matching, explanation creation, and time series analysis. The results show that the planning of etiquette learning through the team teaching model in MIM 6 Nglegok was carried out thoroughly at a work meeting. Teachers compiled etiquette learning materials, shared roles, and agreed on joint learning objectives, prepared human resources, and procured training programs. The implementation of etiquette learning in MIM 6 Nglegok employs a strategy of dividing teaching roles, utilizing lecture methods, group discussions, role-plays, storytelling, and simulations. There are 19 etiquette materials grouped into three concepts: etiquette towards God, etiquette towards oneself, and etiquette towards society. Learning evaluation is carried out comprehensively, both on the student learning process and the effectiveness of collaboration between teachers. Weekly evaluation forums, home visits, and Bengkel Adab programs serve as strategies for problem-solving and continuous improvement. This study presents new scientific findings in the form of a method for cultivating etiquette earnestly, with two teachers in one class, allowing the material to be taught more focused and easily absorbed by students. This study only focuses on one location and a specific discipline, further research can be developed on broader themes.